(untitled) (Research, Society and Development, 2024)
Low-cost and safe food preservation has been a major challenge for the food industry and consumers. The objective of this work was to evaluate the formation of biofilms of lactic acid bacteria (Lactobacillus acidophilus) in wooden vats and their potential for food biopreservation. Wooden vats were used to test biofilm formation of inoculated lactic acid bacteria, monitoring the increase in acidity of the preservative solution and collecting samples of biofilms formed on the walls of the wooden vats to evaluate the lactic acid bacteria count. Studies were carried out to evaluate the potential for inhibiting pathogens, using the microorganisms Escherichia coli, Staphylococcus aureus and Salmonella enterica. The wooden vats allowed the growth of lactic acid bacteria and proved to be an efficient system for the formation of biofilms. Furthermore, the growth of lactic acid bacteria in this system satisfactorily inhibited the growth of potentially pathogenic bacteria.